RANCANG BANGUN KENDALI SUHU DAN TEKANAN PADA EKSTRAKTOR SOXHLET TERINTEGRASI PEMBATAS WAKTU EKSTRAKSI MENGGUNAKAN MIKROKONTROLLER ATMEGA 16 - Medilla Kusriyanto (Teknoin, 2013)
Extraction of compounds in a variety of materials, especially materials crops today are often found as a source of natural medicine. Soxhlet is one tool that is used as a medium of extraction of these compounds. Temperature and pressure as well as the long extraction affects the quality of compound extraction obtained. Control of temperature, pressure and time ekstraski kabanyakan still use manual so that there is an error caused by the user or device measuring. In this paper will be discussed extractor soxhlet integrated with the control system temperature, pressure and restrictions on timing extraction using a microcontroller ATMega 16 so that the extraction process can be run automatically. Control system temperature and pressure using a thermocouple type K which has a limit of measurement 0 - 12000C and pressure sensors MPX5700 which has a limit of measurement of the pressure of 0-700 Kpa. All output of this sensor will be read by the ADC microcontroller ATMega 16 is already integrated with internal ADC with a resolution of 10 Bit. Restrictions on the timing ekstraski done by using timer microcontroller